RECONFIGURING REALITY: A PHILOSOPHICAL INQUIRY INTO THE EPISTEMIC FOUNDATIONS AND METAPHYSICS OF TANTRIC NON-DUALISM - I Gusti Putu Gede Widiana (INTERNATIONAL JOURNAL ON HINDU CULTURE, 2026)
The academic study of tantra has long been dominated by sensationalist accounts emphasizing ritual and antinomian practices, creating a significant gap between popular perceptions and the sophisticated philosophical systems embedded within tantric traditions. While scholars have extensively documented tantric rituals and iconography, the philosophical dimensions—particularly the epistemological foundations and metaphysical structures—remain underexplored in contemporary academic discourse. This gap is problematic because tantric traditions themselves present their practices as expressions of coherent philosophical systems rather than as mere ritualism. This article addresses this gap by investigating the philosophical foundations of tantra, focusing on the transition from mainstream Indian epistemological frameworks toward a distinctive non-dual metaphysics. The study employs a historical-philosophical approach and conceptual analysis of primary texts from the Kashmiri Śaiva Pratyabhijñā tradition and Tibetan Buddhist Vajrayāna, examining their engagement with Yogācāra idealism and their development of distinctive epistemological and metaphysical positions. The findings reveal that tantric philosophy centers on the conception of consciousness as the ultimate reality (prakāśa) accompanied by reflexive awareness (vimarśa), offering a sophisticated idealist system that integrates epistemology, metaphysics, ethics, and soteriology. The article concludes that tantric philosophy provides an alternative model of how reality is constituted and how liberation can be achieved through recognition of the fundamental identity between individual self and absolute reality, with significant implications for cross-cultural philosophical dialogue.